Assessment Report, Banso District, Cameroons Province (Colonial Letters and the Contact of Knowledges, 1928)
This file contains colonial assessment report on Banso District
Keywords: Archives; Colonisation; Letters; Social norms; Discourse analysis; British Colonisation; Colonial Records; Banso; Southern Cameroons; Postcolonial Heritage; Great Britain; Postcolonial Studies